Transplantasi Uterus untuk Mengatasi Absolute Uterine Factor Infertility (AUFI) pada Sindrom Mayer-Rokitansky-Küster-Hauser (MRKH) - Damanik, Lucky Pestauli (PT Kalbe Farma Tbk., 2024)
Infertility caused by the absence of the uterus or its physiological capabilities is called absolute uterine factor infertility (AUFI). One of the causes of AUFI is Mayer-Rokitansky-Küster-Hauser syndrome (MRKH), a congenital abnormality that results in the absence of or failure to develop a uterus, without any interference of secondary sex characteristics. The only proven therapy to overcome infertility in RMKH syndrome is uterine transplantation. However, there are ethical problems with the uterus transplant procedure, especially regarding the nature of the syndrome, which is not a life-saving intervention but is limited to life-enhancing purposes.